Oxidative Stress In Myocardial Infarction - DESAI.VIDYA; SIVA PRABODH; N.V.S.CHOWDARY; RAVI SHEKHAR (International Journal of Pharma and Bio Sciences, 2012)
Myocardial Infarction results from occlusion of the coronary artery and reactive oxygen species have an important role in the pathogenesis of myocardial infarction. The study population contained 56 subjects with Acute myocardial infarction divided into four groups, Group I ,11 patients with Diabetes Mellitus and Hypertension, Group II ,11 patients with Hypertension, Group III 17 patients Non smokers, Group IV 17 patients Smokers and 30 age and sex matched healthy subjects were investigated for Troponin I , Creatine Kinase, CKMB , Lipid profile and plasma MDA . Plasma MDA levels were significantly elevated in all the groups(p<0.001). Study revealed a significant positive association between plasma MDA and Cholesterol (p<0.01;r=0.620) and plasma MDA and Triglycerides (p<0.01;r=0.028) and a negative association between MDA and HDL-cholesterol (p<0.01; r=0.006). A significant increase in MDA and a significant decrease of HDL-C suggest that reactive oxygen species have an important role in the pathogenesis of myocardial infarction.